Автор и рассказчик в книге Э. Лимонова «Мои живописцы»: маска или подлинное Я? - Яновна Пекарь, Яна (SlavVaria, 2024)
Author and narrator in E. Limonov’s book «My Painters»: mask or true self? The article explores the creation of an original mask. This longstanding tradition is acquiring particular relevance at the present time, which is associated with the changed sociocultural situation. The mass reader, under the influence of extra-textual reality, has developed clip thinking, which has led to a very trivial interest of the reader in art. The audience's request to shorten and simplify meanings forces the author to hide his face behind a mask. Using the example of E. Limonov’s book “My Painters” it is shown how the practice of text construction is oriented towards a specific reader and correlates with the commercial specifics of the text. E. Limonov, reducing the historical value of famous paintings, rethinks the sublime world of art, presenting it to the reader as everyday life, filled with tangible elements of everyday life, while he does not take into account the symbolic meaning of works by artists of different times.